Morphological evaluation of the quality of decellularized esophagus in rat - R. Z. Nakokhov; E. A. Gubareva; E. V. Kuevda; A. S. Sotnichenko; I. S. Gumenyuk; A. Kh. Kade; G. M. Mogilnaya; D. P. Puzanov (Вестник трансплантологии и искусственных органов)
The main aim of our investigation was analysis and optimization of the existing protocols of esophagus decellularization in rats, identification of parameters affecting the quality of decellularization and intactness of the native properties of esophageal extracellular matrix (ECM). Materials and methods. We developed a modified decellularization protocol based on detergent-enzymatic method using sodium deoxycholate and DNAse. Results. Morphological evaluation of the obtained decellularized matrices demonstrated the absence of cells and cell elements while mechanical properties of ECM were preserved. Conclusion. The developed protocol of esophagus decellularization is a potential basis for obtaining of tissue-engineered esophagus scaffold constructions.